2017
DOI: 10.1002/gj.2995
|View full text |Cite
|
Sign up to set email alerts
|

Origin of ooids in ooidal‐muddy laminites: A case study of the lower Cambrian Qingxudong Formation in the Sichuan Basin, South China

Abstract: Ooids have been considered the most intriguing component of carbonate rocks, but the formation mechanism of carbonate ooids remains a matter of intense discussion. The lower Cambrian Qingxudong Formation in the southeastern Sichuan Basin contains abundant ooidal‐muddy laminites. Petrographic and sedimentological analyses revealed that these laminites formed in a shallow‐marine environment (preferably along the windward side of the reef‐shoal). Changing energy conditions caused variable supplies of grainy and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Previous studies reported on the general microfacies analysis of Cambrian–Ordovician carbonate facies in the YCP (e.g. Zou et al 2017; Tan et al 2018; Zhang-SC et al 2018; Zhai et al 2019; Fu et al 2020; Gao et al 2021). The present study focused on oolitic and intraclastic grainstones with the aim of identifying sedimentary differentiation due to prevailing wind directions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported on the general microfacies analysis of Cambrian–Ordovician carbonate facies in the YCP (e.g. Zou et al 2017; Tan et al 2018; Zhang-SC et al 2018; Zhai et al 2019; Fu et al 2020; Gao et al 2021). The present study focused on oolitic and intraclastic grainstones with the aim of identifying sedimentary differentiation due to prevailing wind directions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported on the general microfacies analysis of Cambrian-Ordovician carbonate facies in the YCP (e.g. Zou et al 2017;Tan et al 2018;Zhai et al 2019;Fu et al 2020;Gao et al 2021). The present study focused…”
Section: A Sedimentary Differentiationmentioning
confidence: 95%
“…The lower Cambrian Qingxudong Formation, Sichuan Basin, could be a counterexample for giant ooids developed in deepening and moderate-energy subtidal environments affected by episodic hydrodynamic events (Tan et al . 2018).…”
Section: Palaeoenvironmental Reconstruction Of the Lost Cambrian Plat...mentioning
confidence: 99%
“…(Duguid et al 2010). Some Cambrian ooids show different types of microbial activity as well, such as encrusting filamentous cyanobacteria (e.g., Girvanella-cortex ooids; Liu & Zhang 2012) or the presence of microbial microborings, filaments and extracellular polymeric substances or EPS (Tan et al 2018).…”
Section: Oolitic Shoal Complexmentioning
confidence: 99%
See 1 more Smart Citation